2008
DOI: 10.1111/j.1937-8327.2002.tb00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Performance Technology: An Examination of Definitions through Dependent and Independent Variables

Abstract: This definitional paper provides a chronological perspective of human performance technology (HPT) definitions and an evaluation of them in terms of independent and dependent variables. The intent is to compare the definitions with the goals that have been articulated for HPT over the years and to provide one source for past definitions as researchers move forward to continue their study of HPT. The search for definitions extended back to Gilbert in the late 1970s, who provided a foundation; the search reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…In addition, crisis plans could also include workforce development issues such as selection and recruitment plans, training issues of new employees, and retention strategies in the event that portions of the workforce are temporarily relocated or reassigned, as was the case in the New Orleans area after Hurricane Katrina (Woodward, 2006). These suggestions reflect the more systematic perspective taken by performance improvement professionals who can leverage their knowledge of human capital, performance interventions, and systems thinking to enhance business outcomes (Irlbeck, 2002).…”
Section: Leverage Knowledge Of Hpt To Support Crisis Planning Intervementioning
confidence: 95%
“…In addition, crisis plans could also include workforce development issues such as selection and recruitment plans, training issues of new employees, and retention strategies in the event that portions of the workforce are temporarily relocated or reassigned, as was the case in the New Orleans area after Hurricane Katrina (Woodward, 2006). These suggestions reflect the more systematic perspective taken by performance improvement professionals who can leverage their knowledge of human capital, performance interventions, and systems thinking to enhance business outcomes (Irlbeck, 2002).…”
Section: Leverage Knowledge Of Hpt To Support Crisis Planning Intervementioning
confidence: 95%
“…As an interdisciplinary field, it is rooted in and influenced by behaviorist and cognitive psychology, economics, neuroscience, general systems theory, information technology, organizational development, and other bodies of knowledge (Ferond, ; Rosenberg, Coscarelli, & Hutchinson, ; Stolovitch & Keeps, ). While these multifaceted influences make the field dynamic, they also make it more complex to define (Irlbeck, ). The second reason is that the field is relatively young.…”
Section: The Problem Of Defining the Fieldmentioning
confidence: 99%
“…The notion of a s ystematic approach is also a fundamental notion of HPT (Irlbeck, ). The Stolovitch and Keeps (; ) and Rothwell et al () definitional reviews identified systematic as a key attribute of HPT.…”
Section: Previous Reviews Of Hpt Definitionsmentioning
confidence: 99%
“…It has also been influenced by, and remains in support of, a number of other disciplines, such as economics, education, organization development, human resource development, training and development, and cognitive psychology. Irlbeck (2002) analyzed the historical definitions of HPT and identified three recurring themes: a systems approach, references to performance, and a focus on individuals, groups, and organizations. HPT and the International Society of Performance Improvement (ISPI), the publication for HPT, "maintain reference to the human side of the equation by alluding to individuals, groups, and/or organizations" (Irlbeck, 2002, p. 93).…”
Section: New Metacognitive Model For Human Performance Technologymentioning
confidence: 99%